1995
DOI: 10.1071/mf9951021
|View full text |Cite
|
Sign up to set email alerts
|

Genetic relationships of eight species of Pacific tunas (Teleostei: Scombridae) inferred from allozyme analysis

Abstract: A phylogenetic analysis of eight species of Pacific tunas was made after examining allozyme variation at 23 muscle and liver enzymes encoded by 35 loci. The eight species of tuna were: Thunnus alalunga, albacore; T. obesus, bigeye; T. thynnus orientalis, northern bluefin; T. maccoyii, southern bluefin; T. albacares, yellowfin; Auxis thazard, frigate; Euthynnus affiizii kawakawa; Katsuwonus pelamis, skipjack. All species except the northern bluefin were also examined for variation at three eye-specific loci. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
15
1
1

Year Published

1995
1995
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 0 publications
3
15
1
1
Order By: Relevance
“…The present results on mtDNA and nDNA are consistent with allozyme analysis by Sharp and Pirages (1978) and Elliott and Ward (1995) for T. alalunga (ALB), which showed it to be the most divergent member of the genus. Although mtDNA of T. t. orientalis (PNB) is very similar to that of T. alalunga (ALB), the allozyme analysis revealed T. t. orientalis (PNB) to have closest affinity to T. t. thynnus (ANB), T. maccoyii (SBT), and even to the species of yellowfin tuna group.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…The present results on mtDNA and nDNA are consistent with allozyme analysis by Sharp and Pirages (1978) and Elliott and Ward (1995) for T. alalunga (ALB), which showed it to be the most divergent member of the genus. Although mtDNA of T. t. orientalis (PNB) is very similar to that of T. alalunga (ALB), the allozyme analysis revealed T. t. orientalis (PNB) to have closest affinity to T. t. thynnus (ANB), T. maccoyii (SBT), and even to the species of yellowfin tuna group.…”
Section: Discussionsupporting
confidence: 78%
“…Bluefin tunas (ANB and SBT) and species of the yellowfin group (BFT, LTT, and YFT) showing less mtDNA divergence from one another may have emerged -500,000 years ago. Elliott and Ward (1995) indicated that the Thunnus tuna species appear to be genetically much more similar one another than are most congeneric fish species and pointed out that the relationships between bluefin tunas (PNB and SBT) and T. albacares (YFT) are too close to infer the branch orders from their allozyme data. MtDNA divergence between T. t. orientalis (PNB) and T. alalunga (ALB) is comparable with those among T. t. thynnus (ANB), T. maccoyii (SBT), and species of the yellowfin group, suggesting an introgression event to have occurred at similar timing with the emergence of the bluefin tunas and tropical tuna species.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, Sharp & Pirages (1978) and Chow & Kishino (1995) indicated that albacore tunas are highly divergent from all other tunas, suggesting that the Thunnus subgenus is not a monophyletic group. Elliott and Ward (1995) reported that bluefin tunas were much closer to the yellow tuna than to albacore and bigeye tunas, and albacore was the most divergent species in the maccoyii was obtained from the Indian Ocean by Taiwanese fishery observers in 2006 as described by Shiao et al (2008). Thunnus thynnus was caught from Martinique waters of the eastern Caribbean Sea in 2008.…”
Section: Introductionmentioning
confidence: 99%